Erro e ilusão transcendental no primeiro paralogismo da segunda edição da crítica da razão pura - Cruz, Patrícia Fernandes da (2020)
The main objective of this dissertation is to understand the error and transcendental illusion in the paralogism of the substantiality of the second edition in the Critique of Pure Reason. Paralogisms, as part of the transcendental Dialectic, defined by Kant as a “logic of illusion”, are an important point in this investigation, since they are focused on the critique of I think, the only text available for rational psychology, which plays a positive and indispensable function already in the transcendental deduction of Critique. In transcendental deduction, I think is a merely formal condition of all thought and is not, in itself, illusory. Thus, the transcendental Dialectic gains negative contours from the introduction of an aspect of the very nature of reason in relation to the I think: the transcendental illusion that is characterized as inevitable. Beside this illusion, there are errors that are treated as preventable. They do not originate from a lack of attention to logical rules, but are based on transcendental illusion. The first paralogism, in its version B, is taken as paradigmatic in this dissertation. In it, Kant criticizes rational psychology when it states that the mode of existence of the I think (the soul) can be taken as a substance. This statement involves the comprehension that the transcendental illusion is generated from rational principles: one of them is of a logical order - "to find, for the conditioned knowledge of understanding, the unconditioned by which the unity is completed" -, presented by Kant as a subjective need for rational activity; another principle is of a transcendental order - “given the conditioned, the unconditioned is also” - characterized by the claim of objective validity of the same activity. The problem of the relation between these two principles arises insofar as the transcendental principle is defined as illusory. Therefore, the transcendental illusion is based on the assumption that there is objective validity to the soul (I think); that is, that we can find an existing object, while, in fact, this object is unconditioned. The error has its source in the transcendental illusion and occurs when such an illusion leads to a misuse of categories (in this case, the category of substance), which consists in extending them beyond the objects of experience in view of the transcendent objects of reason that are unconditioned. The gain achieved in this dissertation is to clarify the relation between the logical and transcendental principles of reason, a relation that is essential to understand the general explanation of the transcendental illusion.